Analisis Sumber-Sumber Pendapatan Asli Daerah dalam Meningkatkan Kemandirian Fiskal Daerah di Kabupaten Tanjung Jabung Barat - Silvina Silvina; Erni Achmad; Yuliusman Yuliusman (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the contribution of Regional Original Revenue (PAD) sources, the growth of PAD, and the level of regional fiscal independence in Tanjung Jabung Barat Regency during the 2017–2024 period. The PAD sources examined include local taxes, regional retributions, returns from separated regional assets, and other legitimate PAD. The data used in this study are secondary data in the form of Budget Realization Reports (LRA) of Tanjung Jabung Barat Regency for the period 2017–2024, obtained from the Regional Revenue Agency (Bapenda) of Tanjung Jabung Barat and the Directorate General of Fiscal Balance. This research employs a quantitative descriptive approach. The analytical techniques used include contribution analysis of PAD sources (local taxes, regional retributions, returns from separated regional assets, and other legitimate PAD), PAD growth analysis, and fiscal independence ratio analysis. The results indicate that PAD is predominantly contributed by other legitimate PAD, accounting for 62.54% of total PAD, followed by local taxes contributing 26.06%, while regional retributions and returns from separated regional assets contribute relatively low proportions. The growth of PAD during the study period shows fluctuations influenced by economic conditions, including the impact of the COVID-19 pandemic. Furthermore, the level of fiscal independence in Tanjung Jabung Barat Regency is categorized as very low, as reflected in the high dependence on transfer funds from the central government and other governmental assistance.